ESG Integration in Sharia Investment: A Maqāṣid Al-Sharī'ah Perspective on Sharia Mutual Fund Portfolios in Indonesia - Sholikul Hadi; Ade Sofyan Mulazid; Yudi Permana; Abdul Hakim; Dewi Kurniasari; Meirani Rahayu Rukmanda; Rio Kartika Supriyatna (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2026)
: Despite the rapid growth of sustainable finance, the Islamic jurisprudential status of Environmental, Social, and Governance (ESG) integration in Sharia-compliant mutual funds remains unresolved. Existing scholarship treats ESG–Sharia compatibility as a matter of thematic alignment rather than legal obligation, leaving fund managers and regulators without a normative framework grounded in Islamic legal reasoning. This study addresses that gap by determining the ḥukm taklīfī governing ESG integration in Indonesian Sharia mutual funds. A mixed-methods design is embedded within an uṣūl al-fiqh analytical framework. Quantitatively, Pearson correlation and simple linear regression are applied to ten Sharia mutual funds listed on the Indonesia Stock Exchange (2019–2024); qualitatively, in-depth interviews with fund managers, Sharia supervisory board members, and capital market regulators are supplemented by a questionnaire administered to 210 retail investors. Empirical findings serve as the maṇāṭ (operative cause) for a three-stage istinbāṭ sequence: taḥqīq al-maṇāṭ, takyīf al-waqāʾīʿ, and takhrīj al-ḥukm. ESG-integrated Sharia funds generate superior risk-adjusted performance (annualised returns of 8.5–9.7%, Sharpe ratios > 1.10) relative to non-ESG Sharia funds (7.0–7.5%; Sharpe ratio ≈ 0.90), confirming ESG integration as consistent with ḥifẓ al-māl. Subjecting these findings to maqāṣid al-sharīʿah analysis — incorporating Ibn ʿĀshūrʿs articulation of ḥifẓ al-bīʿah alongside the maxims lā ḍarar wa lā ḍirār and darʼ al-mafāsid muqaddam ʿalā jalb al-maṣāliḥ — the study derives a graduated ruling: ESG integration is mandūb as a baseline and attains wājib kifāʼī where conventional Sharia screening demonstrably fails to prevent verifiable environmental or social darar. The governance pillar is already operationally embedded within existing Sharia oversight structures; social screening remains partial and requires extension from exclusionary toward positive maqāṣid-oriented assessment; and environmental integration generates a collective institutional obligation to develop the requisite data infrastructure. The study makes an original contribution to Islamic investment jurisprudence (fiqh al-istithmār) as the first to apply a complete uṣūl al-fiqh derivation to ESG integration in Sharia mutual funds, advancing a juristic proposal for a national Sharia-ESG fatwa framework to be coordinated by DSN-MUI and OJK.